2021
DOI: 10.1093/ibd/izaa336
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Conventional Stool Testing and Multiplex Molecular Panel in Outpatients With Relapse of Inflammatory Bowel Disease

Abstract: Background Differentiating between enteric infection and relapse of inflammatory bowel disease (IBD) is a common clinical challenge. Few studies have evaluated the impact of multiplex gastrointestinal polymerase chain reaction (GI PCR) pathogen panels on clinical practice compared to stool culture. Our aim was to compare the impact of PCR stool testing to conventional stool testing in outpatients presenting with relapse of IBD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…24 In a study of GI PCR testing in patients with HIV, Axelrad et al found that 25% of men who have sex with men patients had multiple gut pathogens regardless of their degree of immunosuppression. 11,25 Our study was not powered to look at specific categories of immunosuppression and it is likely that there was heterogeneity in the degree of immunosuppression within the diverse group of immunosuppressed patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a study of GI PCR testing in patients with HIV, Axelrad et al found that 25% of men who have sex with men patients had multiple gut pathogens regardless of their degree of immunosuppression. 11,25 Our study was not powered to look at specific categories of immunosuppression and it is likely that there was heterogeneity in the degree of immunosuppression within the diverse group of immunosuppressed patients included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal infections are commonly implicated in relapse (flares) of already established IBD (Table 2). [83][84][85][86][87][88] There is considerable overlap between the clinical presentation of enteric infection and IBD flare, suggesting that these conditions may be mutually exclusive or co-exist, further complicating interpretation and causal determination. Current clinical guidelines recommend testing for C. difficile in all patients with IBD who have worsening or new onset diarrhea and testing for CMV in patients with severe active IBD, particularly if there is concomitant steroid use and disease refractory to medical therapy.…”
Section: Gastrointestinal Pathogens In Relapse Of Ibdmentioning
confidence: 99%
“…The utility of GIP in immunocompromised patients has also been documented. In patients with inflammatory bowel disease (IBD), Hong et al 4 showed that GIP testing was associated with increased detection of microbes and lower rates of IBD therapy escalation and endoscopies with no difference in adverse outcomes. GIP testing in hematopoietic stem-cell transplant recipients has been associated with increased identification of infectious pathogens without increasing overall testing cost.…”
mentioning
confidence: 99%